Knowledge of human monkeypox viral infection among general practitioners: a cross-sectional study in Indonesia. (17th February 2020) - Harapan, Harapan; Setiawan, Abdul M.; Yufika, Amanda; Anwar, Samsul; Wahyuni, Sri; Asrizal, Febrivan W.; Sufri, Muhammad R.; Putra, Reza P.; Wijayanti, Nanda P.; Salwiyadi, Salwiyadi; Maulana, Razi; Khusna, Afriyani; et al.
ABSTRACT: After the first, imported, laboratory-confirmed case of monkeypox in human was reported in Singapore on May 2019, countries in Asia started to strengthen disease surveillance systems. One challenge in preventing monkeypox is a lack of knowledge, particularly among healthcare workers. The aim of this study was to assess the knowledge of monkeypox among general practitioners (GPs) in Indonesia. A cross-sectional online survey was conducted. The survey collected participants' knowledge on a 21-item scale and explanatory variables. A two-step logistic regression analysis was employed to assess the predictors of knowledge of monkeypox. A total of 432 GPs were included; 10.0% and 36.5% of them had a good knowledge using an 80% and 70% cutoff point for knowledge domain, respectively. No explanatory variables were associated with knowledge when using 80% cutoff point. Using the lower cutoff, there was lower knowledge among GPs who graduated from universities located in Sumatra or other islands versus Java (adjusted odds ratio (aOR): 0.53; 95%CI: 0.28–0.97, p = 0.041) and among those were older than 30 years compared to younger GPs (aOR: 0.61; 95%CI: 0.39–0.96, p = 0.033). GPs working in private clinics had less knowledge compared to GPs in community health centers (aOR: 0.55; 95%CI: 0.31–0.99, p = 0.047). In conclusion, knowledge of monkeypox among GPs in Indonesia is relatively low in all groups. Increasing knowledge of monkeypox will be key to improving the capacity of GPs to respond to human monkeypox cases and to report into a disease surveillance system.